Micro-scale rapid prototyping by stereolithography - Monneret, S.; Provin, C.; Le Gall, H. (IEEE International Conference on Emerging Technologies and Factory Automation 2001, 2001)
A new process of microstereolithography to manufacture freeform solid three-dimensional micro-components with outer dimensions in the millimetre size range is presented. It corresponds to a layered micromachining, specially suited to rapid prototyping at the micro scale. Different kinds of materials can be employed, like pure polymers or alumina-based composites. The micromachine is mainly composed of a liquid crystal display as a dynamic mask generator and of a broad-band visible light source. The manufacture of complex three dimensional microparts demonstrates the possibilities of the process specially when concerned with composite alumina-based microstructures. Its availability to realise pure sintered alumina microcomponents is also shown.